Endovascular treatment of cerebrovascular stenosis with stent for patients with ischemic cerebrovascular disease. Issue 47 (20th November 2020) - Lin, Kailong; Chen, Liusheng; Wang, Yang; Xu, Yeqiang; Wang, Guanliang; Li, Hongfang; Pan, Yicheng; Ma, Lichun; He, Siyi
Abstract : Abstract: This study aimed to investigate the therapeutic effect of cerebrovascular stent implantation in southwest Chinese patients with ischemic cerebrovascular disease and underlying risk factors for stent restenosis. We made a retrospectively analysis of occurring risk, cerebrovascular lesion, stent implantation, complication treatment, and prognosis of 54 patients with ischemic cerebrovascular disease in our department. A total of 85 stents were implanted into 54 patients, involving 44 of the internal carotid artery system, 34 of the vertebral-basal artery system and 7 of the subclavian artery system. All patients with stenosis were reduced by >70%, with all stenosis complete reduction in 5 (9%) patients and reduction of over 90% in 25 (46%) patients. A total of 50 patients were followed up for 28.5 (21–35) months. The stents in 42 patients exhibited satisfactory shape and location while restenosis occurred in 8 patients. Univariate analysis revealed that hyperlipidemia, hyperuricemia, surgery duration, and total length of hospital stay are significantly correlated with stent restenosis, and hyperlipidemia and hyperuricemia were proven to be independent risk factors for restenosis using logistic regression analysis. Cerebrovascular stent implantation and balloon inflation surgery can assist in abating angiostenosis and improving blood supplement effectively in patients with ischemic cerebrovascular disease. Besides, an overall evaluation, strict care, and regular check-up in perioperative period may reduce the occurrence of complications. Finally, several clinical parameters may need to be highly focused on in surgery for better prognosis.